A first-principles study on the magnetic properties of Sc, V, Cr and Mn-doped monolayer TiS3. Issue 60 (8th June 2016) - Zheng, Huiling; Zhu, Mingfeng; Zhang, Jianmin; Du, Xiaobo; Yan, Yu
Abstract : Substitutional doping of V, Cr and Mn atoms can induce the magnetic moment in monolayer TiS3 . Abstract : The geometrical structure, electronic structure and magnetic properties of Sc, V, Cr, Mn-doped monolayer TiS3 are investigated using first-principles calculations in the framework of density functional theory. The results show that the substitutional doping of Sc, V, Cr and Mn atoms in monolayer TiS3 is possible under Ti poor conditions and all of the doped systems are stable at room temperature. Furthermore, it is found that the ground states of V, Cr and Mn doped systems are magnetic and the magnetic moments induced by the dopant mainly come from the 3d orbitals of the dopants with a partial contribution from the 3p orbitals of neighboring S atoms around the dopants and the 3d orbitals of neighboring Ti atoms around the dopants. In particular, the magnetic coupling between the moments induced by two V and Mn is long-range ferromagnetic and the coupling can be attributed to the hybridization interaction involving polarized electrons, whereas the coupling between the moments induced by two Cr is anti-ferromagnetic. The last result suggests that the substitutional doping of V and Mn atoms can induce the room temperature ferromagnetism in monolayer TiS3 .